2015
DOI: 10.1039/c5ra19107f
|View full text |Cite|
|
Sign up to set email alerts
|

Structure–property relationship in lead-free A- and B-site co-doped Bi0.5(Na0.84K0.16)0.5TiO3–SrTiO3incipient piezoceramics

Abstract: A phase diagram of A- and B-site co-substituted lead-free incipient piezoceramics is schematically constructed on the basis of crystal structure and electromechanical, dielectric and piezoelectric properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 42 publications
(68 reference statements)
4
17
0
1
Order By: Relevance
“…2. The obtained data showed that there were 4 main regions in the spectrum, and this information agrees with many previous reports [18][19][20]. The 4 main regions in the Raman data are as follows:…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…2. The obtained data showed that there were 4 main regions in the spectrum, and this information agrees with many previous reports [18][19][20]. The 4 main regions in the Raman data are as follows:…”
Section: Resultssupporting
confidence: 89%
“…(2) the 260 cm −1 mode is related to Ti−O vibrations. Furthermore, this mode becomes broader and starts splitting into two bands with increasing the additive content, and this may be due to the co-occupancy of different cations (Ti/Ta, Fe) with different sizes at the B-site that results in the distortion of the unit cell [18]; (3) the 450-700 cm −1 region hosts modes that correspond to the vibration of the TiO 6 octahedra. In this region, there is an overlapping band which was slightly separated into two distinct bands for the samples containing higher amount of additive, which demonstrated particular phonon behavior in the structural evolution and a phase mixture; and (4) the high-frequency region above 700 cm −1 feature modes can correspond to A 1 (longitudinal optical) and E (longitudinal optical) overlapping band [19,20], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The TiO 6 octahedra vibration in the range of 450 -655 cm −1 was also separated into three distinct bands in the ceramics (three overlapping bands). This also correlated well with the XRD analysis which indicated that the crystal structure of the leadfree (1-x)BNKT-xBT ceramics transformed from the mixed rhombohedral-tetragonal (for the x = 0 ceramic) into the tetragonal-rich phase (for the x = 0.15 ceramic) [36,37]. Figure 3 shows the FE-SEM micrographs with as sintered surfaces mode of the (1-x)BNKT-xBT ceramics (where x = 0 -0.15).…”
Section: Phase Evolution Raman Analysis and Microstructuresupporting
confidence: 82%
“…(1 -x)(BNT-BT)-xNT (x = 0.01, 0.03, 0.05, 0.10, 0.15) ceramic samples were prepared by traditional solid-state reaction method [8,[24][25][26]. First, the raw powders Bi 2 O 3 (purity 99.0%), Na 2 CO 3 (purity 99.8%), TiO 2 (purity 98.5%), BaCO 3 (purity 99.0%) and Ta 2 O 5 (purity 99.99%) were mixed according to the stoichiometric Where σ 0 is the pre-exponential factor, E a is the activation energy of conduction, k B is the Boltzman constant, 23 1.38 10 / K B k J − = × .…”
Section: Methodsmentioning
confidence: 99%